Nitrogen-Doped Graphene Monolith Catalysts for Oxidative Dehydrogenation of Propane - Liu, Weijie; Cao, Tianlong; Dai, Xueya; Bai, Yunli; Lu, Xingyu; Li, Fan; Qi, Wei (Frontiers in Chemistry, 2021)
It’s of paramount importance to develop renewable nanocarbon materials to replace conventional precious metal catalysts in alkane dehydrogenation reactions. Graphene-based materials with high surface area have great potential for light alkane dehydrogenation. However, the powder-like state of the graphene-based materials seriously limits their potential industrial applications. In the present work, a new synthetic route is designed to fabricate nitrogen-doped graphene-based monolith catalysts for oxidative dehydrogenation of propane. The synthetic strategy combines the hydrothermal-aerogel and the post thermo-treatment procedures with urea and graphene as precursors. The structural characterization and kinetic analysis show that the monolithic catalyst well maintains the structural advantages of graphene with relatively high surface area and excellent thermal stability. The homogeneous distributed nitrogen species can effectively improve the yield of propylene (5.28 % vs. 1.86 %) and lower the activation energy (62.6 kJmol-1 vs. 80.1 kJmol-1) in oxidative dehydrogenation of propane reaction comparing with un-doped graphene monolith. An optimized doping amount at 1:1 weight content of the graphene to urea precursors could exhibit the best catalytic performance. The present work paves the way for developing novel and efficient nitrogen-doped graphene monolithic catalysts for oxidative dehydrogenation reactions of propane.